MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS PARAGRAF DESKRIPTIF DENGAN TEKNIK OUTLINING - Moh. Hanafi (Yayasan Akrab Pekanbaru, 2018)
This research is a final report on classroom action research conducted to know how outlining technique can improve students’ writing ability.The researcher decided to conduct a classroom action researchwhich was done in four stages; planning, implementing, observing and reflecting. The criterion of success was 75% of the students pass the passing grade of 75. In cycle 1, based on the result of the test, 50% of students have passed the passing grade of 75 and the result of the observation showed that the students still had difficulty with outlining technique. Therefore, second cycle was needed to be done. In the second cycle, the result of the test showed that 75% of students had passed the passing grade of 75. Moreover, the result of the observation showed that the students actively participated on the learning process. They also tend to be more enthusiastic in following the lesson. Thereofe,, it can be concluded that the criteria of success had been achieved. It means that the outlining technique was proved to be able to upgrade the students’ ability in writing descriptive paragraph. Keywords: outlining technique, writing ability, descriptive paragraph, classroom action research.